Furmonertinib (AST2818) versus gefitinib as first-line therapy for Chinese patients with locally advanced or metastatic EGFR mutation-positive non-small-cell lung cancer (FURLONG): a multicentre, double-blind, randomised phase 3 study. Issue 11 (November 2022) - Shi, Yuankai; Chen, Gongyan; Wang, Xiang; Liu, Yunpeng; Wu, Lin; Hao, Yanrong; Liu, Chunling; Zhu, Shuyang; Zhang, Xiaodong; Li, Yuping; Liu, Jiwei; Cao, Lejie; et al.
Summary: Background: Furmonertinib (AST2818) is an irreversible, selective, third-generation EGFR tyrosine-kinase inhibitor. We aimed to investigate the efficacy and safety of furmonertinib versus the first-generation EGFR tyrosine-kinase inhibitor gefitinib as first-line treatment in patients with EGFR mutation-positive locally advanced or metastatic non-small-cell lung cancer (NSCLC). Methods: The FURLONG study is a multicentre, double-blind, randomised, phase 3 study done in 55 hospitals across mainland China. We enrolled patients who were aged 18 years or older and had histologically confirmed, locally advanced or metastatic, stage IIIB, IIIC, or IV unresectable NSCLC with EGFR exon 19 deletions or exon 21 Leu858Arg mutation on tissue biopsy confirmed by a central laboratory. Eligible patients were stratified according to EGFR mutation (exon 19 deletions or exon 21 Leu858Arg) and CNS metastases (with or without) and randomly assigned (1:1) to receive either oral furmonertinib (80 mg/day) or oral gefitinib (250 mg/day) in 21-day cycles until disease progression, the occurrence of intolerable toxicities, withdrawal of consent, or other discontinuation reasons judged by the investigators. Investigators, clinicians, participants, independent review centre (IRC) members, the sponsor, and those analysing the data were all masked to treatment allocation. The primary endpoint was IRC-assessed progression-free survival and, along with safety, was analysed in the full analysis set, which comprised all randomly assigned patients who had received at least one dose of study drug. This study is registered with ClinicalTrials.gov, NCT03787992, and is ongoing for survival follow-up. Findings: Between May 30, 2019, and Dec 5, 2019, 750 patients were screened, of whom 358 were randomly assigned to receive either furmonertinib and gefitinib-matching placebo (n=178) or gefitinib and furmonertinib-matching placebo (n=180). 178 patients randomly assigned to furmonertinib and 179 patients randomly assigned to gefitinib were treated and were included in the full analysis set. Median follow-up was 21·0 months (IQR 18·0–23·5) in the furmonertinib group and 21·0 months (18·0–23·5) in the gefitinib group. Median IRC-assessed progression-free survival was 20·8 months (95% CI 17·8–23·5) in the furmonertinib group and 11·1 months (9·7–12·5) in the gefitinib group (hazard ratio 0·44, 95% CI 0·34–0·58; p<0·0001). Treatment-related adverse events of a grade 3 or more occurred in 20 (11%) of 178 patients in the furmonertinib group and in 32 (18%) of 179 patients in the gefitinib group. Treatment-related serious adverse events were reported in ten (6%) patients in the furmonertinib group and in 11 (6%) patients in the gefitinib group. Ten (6%) patients in the furmonertinib group and three (2%) patients in the gefitinib group died due to adverse events, which were all judged to be possibly unrelated to study treatment by the investigators. Interpretation: Furmonertinib showed superior efficacy compared with gefitinib as first-line therapy in Chinese patients with EGFR mutation-positive NSCLC, along with an acceptable safety profile without new signals. Furmonertinib is a new potential treatment option for this population. Funding: Shanghai Allist Pharmaceuticals and the China National Major Project for New Drug Innovation. Translation: For the Chinese translation of the abstract see Supplementary Materials section.